From Bullying to Cyberbullying: Educational Impacts and Prevention Strategies in Indonesia - Arshy Prodyanatasari; Lauretha Devi Fajar Vantie (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
Cyberbullying has become a critical issue in the digital era, significantly impacting the mental health and social well-being of adolescents. This study aims to analyze the transformation of bullying from traditional school environments to cyberspace, with a focus on its psychological, academic, and social impacts, as well as prevention strategies. Using a comprehensive literature review, the study synthesizes findings from various sources, particularly those relevant to the Indonesian context. The results reveal that cyberbullying contributes to severe mental health issues such as depression, anxiety, and social isolation, alongside reduced academic performance. Key contributing factors include anonymity in digital interactions, lack of digital etiquette education, and cultural acceptance of violence. The study emphasizes the need for holistic prevention strategies involving schools, parents, and communities, including education on digital citizenship, strict anti-bullying policies, and psychological support for victims. This research provides valuable insights for developing effective interventions and fostering a safer digital environment for adolescents.